Unveiling Effectiveness of Lean Construction Practices: A Comprehensive Study through Surveys and Case Studies - Mughees Aslam; Edmund Baffoe-Twum; Muhammad Ahmed; Aman Ulhaq (Salehan Institute of Higher Education, 2024)
Construction projects frequently encounter challenges such as stagnant productivity, excessive waste, cost overruns, and delays, contributing to sustainability issues. In response to these issues, Lean Construction (LC) has emerged as a methodology aimed at eradicating inefficiencies and wasteful practices. However, the construction industry has been slow to embrace LC, primarily due to a lack of comprehensive evaluations regarding its real-world effectiveness. This study seeks to thoroughly assess the effectiveness of LC when implemented in construction projects in Pakistan. The research involved conducting a survey among experts in the construction industry, utilizing a comprehensive questionnaire to evaluate the extent of LC adoption and its impact on construction project performance. The collected data underwent rigorous statistical analysis to ascertain the influence of LC practices on project outcomes. To validate the survey results, the study selected five case study projects for in-depth analysis. These case studies assessed how well the projects adhered to LC principles and examined the resulting effects on project delays, cost overruns, quality issues, rework, and health-related concerns. The findings consistently confirmed that a higher level of adherence to LC principles led to significant reductions in project delays, cost overruns, quality issues, and health-related problems. This analysis strongly supports the notion that a more extensive adoption of LC practices results in substantial improvements in project performance. By presenting these compelling results, this study offers valuable insights to the construction industry, providing a clearer path for the effective integration of LC practices. Doi: 10.28991/CEJ-2024-010-04-09 Full Text: PDF